Dynamics of replication origin over-activation - Fu, Haiqing; Redon, Christophe E; Utani, Koichi; Thakur, Bhushan; Jang, Sangmin; Marks, Anna B; Zhuang, Sophie; Lazar, Sarah B; Rao, Mishal; Mencer, Shira; Gross, Jacob M; Lorinc Pongor; et al. (bioRxiv, 2020)
We determined replication patterns in cancer cells in which the controls that normally prevent excess replication were disrupted ("re-replicating cells"). Single-fiber analyses suggested that replication origins were activated at a higher frequency in re-replicating cells. However, nascent strand sequencing demonstrated that re-replicating cells utilized the same pool of potential replication origins as normally replicating cells. Surprisingly, re-replicating cells exhibited a skewed initiation frequency correlating with replication timing. These patterns differed from the replication profiles observed in non-re-replicating cells exposed to replication stress, which activated a novel group of dormant origins not typically activated during normal mitotic growth. Hence, disruption of the molecular interactions that regulates origin initiation can activate two distinct pools of potential replication origins: re-replicating cells over-activate flexible origins while replication stress in normal mitotic growth activates dormant origins.